Are hospitality graduates making too many compromises? What they give up may lead to turnover. Issue 2 (2nd April 2016) - Brown, Eric A.; Bosselman, Robert H.; Thomas, Nicholas J.
ABSTRACT: The purpose of this research was to examine if differences between actual experiences of hospitality graduates and the perceived importance they placed on career factors can lead to turnover intent. The researchers surveyed hospitality graduates from the last 10 years about what they find important in selecting a career and what they are experiencing, or have experienced, in their career. Findings indicate as hospitality graduates rate certain factors more important, or experience factors less in their career, the differences become larger and their turnover intentions rise.